PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH DAN PRESTASI BELAJAR EKONOMI SISWA - Purdianti (DIADIK, 2023)
This study aims to determine the effectiveness of applying the problem-based learning model to improve problem-solving abilities and economic learning achievements of Class XI MIPA students at SMA Negeri 5 Bengkulu City. The method used in this research is classroom action research and experimental methods. This research was conducted in 2 cycles and continued with a quasi-experiment. In carrying out the research, the researcher was assisted by an observer who is an economics teacher at SMAN 5 Bengkulu City. The results of the study show that 1) The application of the problem-based learning model can be used to improve students' problem-solving skills in economics learning, 2) The application of the problem-based learning model in the economics learning process can improve student learning outcomes at SMAN 5 Bengkulu City, 3) Application problem-based learning learning models can improve the effectiveness of student learning